Comprehensive Review of Nursing Collaboration, Skill Development, And Its Role in Multidisciplinary Teams - Al Taymani, Kholod Yaqut; Albalawi, Suhaila Salmah; Alwabsi, Amal Zaidane; Albalawi, Ahlam Zedan; Albalawi, Hanadi Hamdan; Albalawi, Alanoud Faraj Hmoud; Al-Balawi, Salwa Salem Falih; Albalawi, Faten Faleh; Albalwi, Adel Hamoud Sirhan; Al balawi, Tahany Olyan Mohamed (Journal of Ecohumanism, 2024)
Nursing collaboration is crucial in the multidisciplinary health care team practice and promotes the improvement in health practice skills, hence improving the outcome of the care of the patients. This review aims to establish a critical understanding and appreciation of the nurses in a team-based healthcare model within different practice environments concerning the various skills involved and the difficulties encountered. The paper synthesizes recent research evidence and best practice cases with figures and tables to offer practical implications for practicing healthcare professionals and policymakers.